“LA DESPENALIZACIÓN DEL SEGUNDO INCISO DEL ART. 275 DEL CÓDIGO ORGÁNICO INTEGRAL PENAL, COMO UNA EXPRESIÓN DEL PRINCIPIO DE MÍNIMA INTERVENCIÓN PENAL” - Piña Uchuari, María José (2020)
In a Constitutional State of rights and justice, such as the Ecuadorian State, the punitive power of the State is limited, which is why the Criminal Law is responsible for the protection of legal property, but its intervention in society is not necessary when such protection can be achieved through other means, the least harmful, for individual rights and especially human dignity. It is a requirement of the “principle of maximum possible utility” for victims in terms of reparation, which must be combined with the “minimum necessary suffering” for criminals, to receive the response from ius puniendi, which must be sustained in the proportionality. One of the limits of the sanctioning power constitutes the principle of minimal criminal intervention, which reveals a modern conception of intellectuals of Criminal Law, who, as fundamental support, indicate fundamentally that the penalty of imprisonment in particular, and the punitive law in In general, they have not resolved the social conflicts generated by the crime. Therefore, they advocate the establishment of a criminal law that exclusively protects the most relevant legal assets of collective interest, and only when the different means of social control are insufficient or have failed to protect or protect them. This principle, also known as the last ratio, postulates the need to restrict the intervention of the Criminal Law to a maximum, reserving it only for cases of serious attacks on the rules of social coexistence that cannot be regulated by other social control mechanisms. The principle of minimal criminal intervention means the legal obligation of the criminal justice system through its operators to act by moving the punitive state - 8 - apparatus, only when transcendental legal assets of integral relevance of the damage have been injured, through the civil route or administrative. The principle of minimum intervention, which is part of the principle of proportionality or prohibition of excess, whose requirement is based on the double character offered by Criminal Law: a) Being a fragmentary right, as long as all legal assets are not protected, but only those that are important for social coexistence, also limiting this guardianship to those behaviors that attack those goods more intensely; b) Being a subsidiary right that, as a final ratio, must operate only when the legal order cannot be effectively preserved and restored by means of solutions less drastic than the criminal sanction. (…) The doubly fragmentary nature of criminal law, to which we have referred, as an inspiring principle of the material concept of crime, not only requires the protection of the most important legal assets, but also that such protection be dispensed only against attacks more important and reprehensible and exclusively to the extent necessary. The principle of minimum criminal intervention, has its substantial effect as of October 20, 2008, with the validity of our new Constitution, where it is assigned directly the attribution so that the Prosecutor's Office conducts the investigation ex officio or at the request of a party, pre-procedural and criminal procedure, during the process will exercise public criminal action subject to the principles of opportunity and minimal criminal intervention, with attention to the public interest and the rights of the victims. The same has been considered in the Organic Integral Criminal Code, since 2014, when expressly acknowledging: “… Article 3.-Principle of minimum - 9 - intervention. - Criminal intervention is legitimized as long as it is strictly necessary for the protection of people. It is the last resort, when extrapenal mechanisms are not enough ”, in short, the entire Constitutional and Legal legal system, has considered as the most suitable option, the activation of criminal minimalism through the principle of minimal intervention, tending to rationalize this system criminal, criminally protecting the most relevant legal assets of the human being and using Criminal Law, as the last resort of the State, to sanction deviant behavior, having as the main premise, the obligation of the State to promote the resocialization of people. The catalog of criminal offenses has been expressly included in the Comprehensive Organic Criminal Code, aimed at protecting personal and / or collective legal assets, within Chapter V, under the exercise of legislative configuration by the assemblyman, the crimes against citizen responsibility and in its first section to crimes against effective judicial protection, being integrators of those crimes of prevarication, prejudice, false testimony, procedural fraud, evasion, among others, but it has also been recognized the crime of entry of articles prohibited in Article 275 of the COIP, on which the present investigation is concerned. Ecuador, having considered Criminal Law as a mechanism of social control, with the possibility of applying ius puniendi to people, imposing sentences deprived of liberty for the offenses they commit, assumes in parallel the responsibility of rehabilitating people in conflict with The Law, since our State has not recognized indefinite penalties in criminal law. - 10 - Article 35 of the Constitution of the Republic of Ecuador recognizes persons deprived of liberty as vulnerable, being members of the State's priority attention groups. One of the mechanisms for the protection of their rights, is the recognition of the criminal type of Art. 275 of the Organic Integral Criminal Code, has considered: “Entry of prohibited items. The person who enters, by himself or through third parties, the centers of deprivation of liberty, alcoholic beverages, substances cataloged and subject to control, weapons, cell phones or communication equipment, prohibited goods or objects attached to the body or its garments of dressing, will be punished with imprisonment of one to three years. The same penalty applies in the event that the objects referred to in the preceding paragraph, are located inside the social rehabilitation centers or in the possession of the person deprived of liberty ”, however, the second subsection of The norm constitutes a negative expression of the minimum criminal intervention, recognized in Art. 195 of the Constitution, since it is the responsibility of the State to guarantee the rights of persons deprived of liberty, through correct controls and not displacing the criminal responsibility for their actions and omissions to those who are vulnerable and members of the priority care groups. Based on the foregoing, I consider the decriminalization of the second subsection of Art. 275 of the Organic Integral Criminal Code important, so that the possession of prohibited objects in prisons is considered as an administrative offense and not as a criminal offense, as a expression of the minimum criminal intervention, recognized constitutionally.